Unraveling the genetic evolution of SARS-CoV-2 Recombinants using mutational dynamics across the different lineages - Ravi, Varsha; Shamim, Uzma; Khan, Md Abuzar; Swaminathan, Aparna; Mishra, Pallavi; Singh, Rajender; Bharali, Pankaj; Chauhan, Nar Singh; Pandey, Rajesh (Frontiers in Medicine, 2024)
Introduction: Recombination serves as a common strategy employed by RNA viruses for their genetic evolution. An extensive genomic surveillance during COVID-19 pandemic has reported SARS-CoV-2 recombinant strains indicating recombination events during the viral evolution. This study introspects the phenomenon of genome recombination through tracing the footprint of prominent lineages of SARS-CoV-2 at different time points in the context of on-going evolution and emergence of Recombinants. Method: Whole Genome Sequencing was carried out for 2516 SARS-CoV-2 (discovery cohort) and 1126 (validation cohort) using nasopharyngeal samples collected between the time-period of March 2020 to August 2022, as part of genomic surveillance program. The sequences were classified according to the different lineages of SARS-CoV-2 prevailing in India at respective time points. Results: Mutational diversity and abundance evaluation across the 12 lineages identified 58 recombinant sequences as harboring the least number of mutations (n=111), with 14 low frequency unique mutations with major chunk of mutations coming from the BA.2. The spontaneously/dynamically increasing and decreasing trends of mutations highlight the loss of mutations in the Recombinants that were associated with the SARS-CoV-2 replication efficiency, infectivity and disease severity, rendering them functionally with low infectivity and pathogenicity. Linkage Disequilibrium (LD) analysis revealed that mutations comprising the LD blocks of BA.1, BA.2 and Recombinants, were found as minor alleles or as low frequency alleles in the LD blocks from the previous SARS-CoV-2 variant samples, especially Pre-VOC. Moreover, a dissipation in the size of LD blocks as well as LD decay along with high negative regression coefficient (R squared) value was demonstrated in the Omicron, BA.1 and BA.2 lineages, which corroborated with the breakpoint analysis. Conclusion: Together, the findings help to understand the evolution and emergence of Recombinants after the Omicron lineages, more so for sustenance and adaptability, to maintain the epidemic spread of SARS-CoV-2 in the host population already high in immunity levels.